Thrombolysis with an Escherichia coli-Produced Recombinant Plasminogen Activator (BM 06.022) in the Rabbit Model of Jugular Vein Thrombosis - Martin, Ulrich; Fischer, Stephan; Kohnert, Ulrich; Opitz, Ulrich; Rudolph, Rainer; Sponer, Gisbert; Stern, Anne; Strein, Klaus (Thrombosis and Haemostasis, 1991)
The recombinant plasminogen activator BM 06.022 consists of the kringle 2 and the protease domains of human t-PA and is unglycosylated because of the expression in Escherichia coli The thrombolytic and pharmacokinetic properties as well as the hemostasis effects of BM 06.022 were investigated in the rabbit model of jugular vein thrombosis. The thrombi were 125I-fibrin labeled. Intravenous bolus injection of 50, 100, 200, and 400 kU/ kg BM 06.022 or 400, 800, and 1600 kU/kg alteplase over 15 s to six rabbits/dose produced a dose-dependent increase of thrombolysis determined 2 h post injection. The dose-response curve of BM 06.022 was located left compared with that of alteplase. The effective dose of 50% thrombolysis (ED50) obtained by half-logarithmic regression analysis was 163 kU/kg (=0.28 mg/kg) for BM 06.022 and 871 kU/kg (= 1.09 mg/kg) for alteplase. At equipotent doses (50% thrombolysis), the residual concentration of fibrinogen was 74.2% and 76.5%, that of plasminogen 66.7% and 69.4%, and that of α2-antiplasmin 47.3% and 46% for BM 06.022 and alteplase, respectively. Pharmacokinetic analysis for plasma activity at a dose of 400 kU/kg revealed a half-life of 18.9 ±1.5 min for BM 06.022, whereas alteplase was distributed with a half-life of 2.1 ± 0.1 min, accounting for 86.7 ± 1.9% of the total AUC, followed by a β-phase with a half-life of 13.8 ± 0.9 min. Plasma clearance of BM 06.022 was 4.7 ± 0.7 ml min-1 kg-1 compared with 20 ±1.2 ml min-1 kg-1 for alteplase. Due to its lower clearance rate, we conclude that BM 06.022 requires a 5.3-fold lower activity dose than alteplase to achieve an effect of 50% thrombolysis in rabbits. At equipotent doses, BM 06.022 is fibrin selective to the same degree as alteplase.